Late retroperitoneal hematoma with abscess formation following laparoscopic staging of endometrial cancer - Joao Casanova; Renee Vina G. Sicam; Joana Moreira-Barros; Kuan-Gen Huang (Wolters Kluwer Medknow Publications, 2018)
Herein, we report a case of a 63-year-old, nonobese, woman who underwent laparoscopic surgical staging for endometrial cancer with pelvic and para-aortic lymph node dissection. After being discharged, the patient presented to the emergency department with fever and abdominal pain, 1 week after the procedure. Abdominal tenderness, fever, and anemia were the key clinical and laboratory findings. A computed tomography (CT) scan revealed a cystic mass with air bubbles, located in the right iliopsoas region. The features were consistent with an infected hematoma at the right iliopsoas region, which was managed with antibiotics and CT-guided pigtail drainage. Laparoscopic surgical staging for endometrial cancer has been shown to have fewer early complications than open surgery. However, complications can still occur in the most experienced hands. Abscess arising from hematomas after laparoscopic surgical staging can be managed adequately with noninvasive CT-guided drainage.